The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1038/ni1110
|View full text |Cite|
|
Sign up to set email alerts
|

The ubiquitin-modifying enzyme A20 is required for termination of Toll-like receptor responses

Abstract: A20 is a cytoplasmic protein required for the termination of tumor necrosis factor (TNF)-induced signals. We show here that mice doubly deficient in either A20 and TNF or A20 and TNF receptor 1 developed spontaneous inflammation, indicating that A20 is also critical for the regulation of TNF-independent signals in vivo. A20 was required for the termination of Toll-like receptor-induced activity of the transcription factor NF-kappaB and proinflammatory gene expression in macrophages, and this function protected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
906
1
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,002 publications
(943 citation statements)
references
References 41 publications
19
906
1
3
Order By: Relevance
“…Therefore, other factors need to be investigated to explain the differences. It has been reported that A20, which acts together with Itch, Tax1bp1 and RNF11 in a ubiquitin-editing protein complex [20], inhibits both TNF-and TLR-induced responses [18,19]. For this reason we hypothesised anew that these genes were expressed to a greater extent in C57BL/6 compared to BALB/c mice but again, no significant differences could be detected before or after LPS treatment.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Therefore, other factors need to be investigated to explain the differences. It has been reported that A20, which acts together with Itch, Tax1bp1 and RNF11 in a ubiquitin-editing protein complex [20], inhibits both TNF-and TLR-induced responses [18,19]. For this reason we hypothesised anew that these genes were expressed to a greater extent in C57BL/6 compared to BALB/c mice but again, no significant differences could be detected before or after LPS treatment.…”
Section: Discussionmentioning
confidence: 87%
“…Therefore, the contractile responses to carbachol, 5-HT and bradykinin were studied on tracheal segments, fresh or following in vitro exposure to TNFα, polyinosinic:polycytidylic acid (poly I:C) or lipopolysacharide (LPS) for 4 days (activating TNF receptor, TLR3 and TLR4 pathways respectively) while maintained under normal tissue-culture conditions. To evaluate whether altered expression of signalling proteins contributed to differences in the inflammatory response of tracheal segments from C57BL/6 and BALB/c mice, mRNA levels of TLR, the pivotal inflammatory signal transduction proteins JNK, p38 and p65, together with the critical negative regulators of inflammation A20, Itch, Tax1bp1 and RNF11 [18,19], were quantified in tracheal smooth muscle strips.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that A20 HET does not result in hyperactivation of the innate or adaptive immune system as homozygous KO does. 13,33 However, intrahepatic levels of TNF and IL-6 following PH were excessively higher and prolonged in HET versus WT livers 4d post PH, likely contributing to derailed LR. 17 This indicates that maladaptive inflammatory responses in HET mice only unveil following injury (in this case PH), and remain contained to the site of injury (here the liver) as systemic inflammation did not worsen.…”
Section: Discussionmentioning
confidence: 99%
“…The N-terminal deubiquitinating domain of A20 mediates the removal of K63-polyubiquitin chains from RIP1, whereas the C-terminal zinc finger domain catalyzes RIP1 K48-polyubiquitination, thereby targeting RIP1 for proteasomal degradation [7]. Similarly, A20 has been shown to inhibit lipopolysaccharide (LPS)-induced NF-B activation by de-ubiquitinating K63-polyubiquitinated TRAF6 [8], but A20-mediated K48-ubiquitination of TRAF6 has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%